Moral Disengagement and Psychopathy: A Study on Offenders in Italian Jails. Issue 5 (3rd September 2017) - Petruccelli, I.; Barbaranelli, C.; Costantino, V.; Gherardini, A.; Grilli, S.; Craparo, G.; D'Urso, G.
Abstract : This article investigates mechanisms of moral disengagement and psychopathy in offender detainees (sex offenders and non-sex offenders). In particular, this article investigates whether, in all offenders, moral disengagement and psychopathy are correlated, if there are any differences between sex offenders and non-sex offenders as to psychopathy, and if there are any differences between rapists and child molesters in regard to their levels of psychopathy. The results indicate that, in all offenders, levels of moral disengagement are associated with levels of psychopathy, while sex offenders are more selfish, more insensitive and less remorseful than non-sex offenders. It is also found that rapists display more antisocial behaviour problematic elements in their lifestyle than child molesters. As well as increasing the dedicated literature, studying the mechanisms and characteristics of offenders – and of sex offenders in particular – may be of considerable importance for the promotion of effective and targeted treatment strategies.